2022
DOI: 10.1364/jocn.451516
|View full text |Cite
|
Sign up to set email alerts
|

Advances in SDN control and telemetry for beyond 100G disaggregated optical networks [Invited]

Abstract: This tutorial considers the evolution of software-defined networking (SDN) control for optical transport networks (OTNs) in disaggregated scenarios, focusing on its requirements and challenges when applied to “beyond 100G” networks, a term that jointly refers to the use of coherent technology, data rates beyond 100G, and the evolution of OTN standards to support rates such as 200G, 400G, or 800G. The tutorial covers use-case-driven SDN development, new challenges, and requirements, such as the need to account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In case that at least one feature is out of range, count is reset and the input features Φ are returned (lines 9-11). Otherwise, count is increased and, if maxcount is reached, it means that a period of low frequency collection has been achieved, so count needs to be reset to 0 and averaged features Φ avg are returned (lines [13][14][15]. Note that in both previous cases, send is True in order to indicate that features must be conveyed.…”
Section: Data Summarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In case that at least one feature is out of range, count is reset and the input features Φ are returned (lines 9-11). Otherwise, count is increased and, if maxcount is reached, it means that a period of low frequency collection has been achieved, so count needs to be reset to 0 and averaged features Φ avg are returned (lines [13][14][15]. Note that in both previous cases, send is True in order to indicate that features must be conveyed.…”
Section: Data Summarizationmentioning
confidence: 99%
“…Other telemetry pipelines have been proposed, like hierarchical ones for scalability purposes. See, e.g., the tutorial in [15] which details the challenges and requirements for optical telemetry and streaming. In addition, the authors in [16] demonstrated a modular telemetry broker for the remote collection and exchange of telemetry data.…”
Section: Introductionmentioning
confidence: 99%
“…Optical networks are complex systems that may use different optical fiber types and devices that can all provide a variety of system parameters. In this regard, optical telemetry data [1] collected from different observation points, such as optical coherent receivers, can not only help to minimize the required design margins therefore maximizing the overall network capacity, but also be useful for many other use-cases, from transmission system characterization to real-time autonomous networking, and failure management, just to mention a few. More precisely, the advances in optical coherent receivers and digital signal processing (DSP) have not only paved the way to improve the overall optical network performance, but can also provide a large set of performance parameters and signal measurements that are available for collection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Telemetry is an attractive technology to provide comprehensive and accurate awareness of optical network performance, potentially leading to remarkable traffic engineering optimization or accurate failure detection [1]. However, current telemetry systems typically suffer from substantial scalability issues due to the large amount of data processed at the centralized telemetry collector [2].…”
Section: Introductionmentioning
confidence: 99%